Metal–organic frameworks for dye sorption: structure–property relationships and scalable deposition of the membrane adsorber. Issue 36 (30th August 2018) - Chi, Heng-Yu; Hung, Shao-Hsiang; Kan, Ming-Yang; Lee, Li-Wei; Lam, Chon Hei; Chen, Jiun-Jen; Kang, Dun-Yen
Abstract : The metal–organic framework-based membrane adsorber is applied to sorption of dye molecules. Abstract : Metal–organic frameworks (MOFs) are increasingly being used for the sorption of dye molecules. Researchers have demonstrated the high sorption performance of several MOFs; however, their structure–property relationships have yet to be fully elucidated. Furthermore, the lack of a generalized deposition method for the fabrication of MOF membranes limits the industrial-scale application of MOF-based sorbents. In this work, we used a polymorphic system with three MOFs, ZIF-8, ZIF-L, and dia(Zn), to identify the key factors affecting the dye sorption performance. We found that ZIF-L, which possesses free imidazole molecules that leach into water during sorption, had the highest sorption capacity for the dye molecule rose bengal. We developed a wet deposition method for the creation of ZIF-L membranes on a porous alumina substrate using stabilized suspensions of ZIF-L. Tubular alumina supports cast with ZIF-L were used as a membrane adsorber for the removal of rose bengal under continuous-flow conditions. Finally, we investigated the influence of the membrane adsorber synthesis conditions on the sorption characteristics.